2022
DOI: 10.1101/2022.05.13.491887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synonymous codon usage regulates translation initiation

Abstract: Synonymous codon usage regulates gene expression such that transcripts rich in optimal codons produce significantly more protein than their nonoptimal counterparts. A major unresolved issue has been understanding the mechanisms by which synonymous codons regulate gene expression. We and others have previously shown that nonoptimal codons slow translation elongation speeds and thereby trigger mRNA degradation. However, differences in transcript abundance are not always sufficient to explain differences in prote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
(164 reference statements)
1
4
0
Order By: Relevance
“…Collectively, these observations lead us to propose that slow elongation limits translation initiation through an unknown, active mechanism. This model is corroborated by a recent report identifying depletion of cap binding proteins from non-optimal reporter transcripts; our results align with the observations of lower initiation in that study (Barrington et al 2022). The discovery of specific feedback on initiation in response to ribosome stalls (Hickey et al 2020; Juszkiewicz et al 2020; Sinha et al 2020) makes it plausible that an analogous mechanism could function on slow but non-stalled ribosomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Collectively, these observations lead us to propose that slow elongation limits translation initiation through an unknown, active mechanism. This model is corroborated by a recent report identifying depletion of cap binding proteins from non-optimal reporter transcripts; our results align with the observations of lower initiation in that study (Barrington et al 2022). The discovery of specific feedback on initiation in response to ribosome stalls (Hickey et al 2020; Juszkiewicz et al 2020; Sinha et al 2020) makes it plausible that an analogous mechanism could function on slow but non-stalled ribosomes.…”
Section: Discussionsupporting
confidence: 93%
“…A distinct pathway in which collided ribosomes inhibit translation initiation has recently been identified in mammalian cells, although this specific pathway is not thought to operate in yeast, which lack a homolog of a key component, 4EHP (Hickey et al 2020; Juszkiewicz et al 2020; Sinha et al 2020). Recent work has demonstrated that slow elongation, even without collisions, can limit initiation to decrease protein output in human and fly cells (Barrington et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between reporters enriched in optimal or nonoptimal codons tend to be greater at the protein level than at the RNA level, supporting translation efficiency differences (12,13,29). It was also recently proposed that enrichment of nonoptimal codons might repress translation initiation (30).…”
Section: Codon Optimalitymentioning
confidence: 90%
“…However, significant variance introduced in translation may obscure noise suppression at the transcriptional level. Other forms of regulation such as translational control and protein-based circuits may be coupled with ComMAND to control expression across the Central Dogma [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%